Some Features of Clinical and Functional Indicators of Myopia in Children in the Republic of Karakalpakstan - Kurbanazarov, M.; Abdullaeva, N. (Asian Pacific Journal of Environment and Cancer, 2021)
The Southern Aral region is characterized by adverse environmental factors that affect human health, including the organ of vision. The comparative estimation of myopia clinical course peculiarities among 333 children aged 2 to 18 years living in the Southern Aral of Karakalpakstan and Samarkand region of Uzbekistan was carried out using the general clinical and ophthalmological methods. In the Southern Aral region, the complicated course of myopia and the proportion of congenital myopia in children was relatively higher than in the control group, which in turn is the cause of the aggravated course of myopia. Further more, extraocular pathology in myopia patients was more frequent among children living in the Southern of the Aral region (over 80%) than in the ecologically favorable area (less than 50%). The obtained data should be considered for drawing up a regional plan for the development and functioning of the children’s ophthalmological service of Karakalpakstan based on elaborating an integrated approach to prevent myopia occurrence and treatment, taking into account residence region and children health.